Development of Data Warehouse for Financial Report in Faculty of Science, Naresuan University - Songsiri, Kittipong; Tamee, Kreangsak (Journal of Applied Informatics and Technology, 2022)
Data warehouse technology is useful for managing large data. The purpose of them are analyzing organization’s datasets to formulate a strategy and direction of the organization. In this paper have present method of the development of data warehouse based on Ralph Kimball's methodology, starting from the study of the data source. Process of Extraction, Transformation and Loading (ETL) until we finished to get for summary financial data warehouse of Faculty of Science, Naresuan University. That they have problem about reporting from OLTP database that use for large data of financial management system. We using the data warehouse which is an OLAP database instead report function to analyze and follow up on the disbursement process more conveniently. In the future, data warehouse technology can also be used to analyze data in other fields within the Faculty of Science as well.